2020
DOI: 10.1111/are.14540
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary carob (Ceratonia siliqua) syrup on blood parameters, gene expression responses and ammonia resistance in tilapia (Oreochromis niloticus)

Abstract: In this study, carob (Ceratonia siliqua) syrup was supplemented in the diet of tilapia (Oreochromis niloticus), and its effects on growth performance, immunological and serum biochemical parameters, gene expression responses and ammonia resistance of the fish were investigated. Carob syrup was added to the fish diet in ratios of 0%, 5%, 2.5%, 1.25% and 0.625%, such that five different diets were prepared: control, Cerat5000, Cerat2500, Cerat1250 and Cerat625 respectively. The fish were fed with experimental di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“…Commercial pods syrup was supplemented to fi sh (Tilapia, Oreochromis niloticus) as part of meals that contained fi xed amounts of other food ingredients. Carob syrup had clear positive effect on immune biomarkers [90].…”
Section: Immune Systemmentioning
confidence: 94%
See 1 more Smart Citation
“…Commercial pods syrup was supplemented to fi sh (Tilapia, Oreochromis niloticus) as part of meals that contained fi xed amounts of other food ingredients. Carob syrup had clear positive effect on immune biomarkers [90].…”
Section: Immune Systemmentioning
confidence: 94%
“…Commercial pods syrup was supplemented to fi sh (Tilapia, Oreochromis niloticus) as part of meals that contained fi xed amounts of other food ingredients. Carob syrup lowered the concentrations of superoxide dismutase [90]. Ethanolic extract of ripe seeds was prepared and it's capacity was tested with DPPH, ABTS, FRAP and CUPRAC methods [91].…”
Section: Antioxidantmentioning
confidence: 99%
“…The main nutrients in complementary food items were added into the complex system of OPFRs and JTR protein and the competitive combination of nutrients and OPFRs molecules was used to restrict or reduce the human health risks of OPFRs. Various supplements have been used in the past to improve the toxicity risks of biological receptors exposed to contaminants (Zhang et al 2018;Rajabiesterabadi et al 2020;Yilmaz, 2020). The binding of OPFRs molecules to JTR in the special population was a key step in its joint neurotoxicity, reproductive toxicity, and ED toxicity (Chen et al 2015;Sun et al 2016;Baldwin et al 2017;Gu et al 2018).…”
Section: Screening Of Cfss Based On MD Simulations To Regulate Human Health Risks In Pregnant Womenmentioning
confidence: 99%
“…Abdel-Tawwab et al 2018;Hamed and Abdel-Tawwab, 2017;Hoseini et al 2018aHoseini et al , 2018b.Hoseini et al found that myrcene or menthol inclusive diet inhibited ammonia-induced tissue damage, anemia, and oxidative stress responses in common carps(Hoseini et al 2019). Also, plant supplements such as garlic(Yousefi et al 2020), artemisia annulis(Taheri Mirghaed et al 2020), olea europea(Rajabiesterabadi et al 2020), ceratonia silique(Yilmaz, 2020), phytochemicals such as 1, 8 cineole(Taheri Mirghaed et al 2019), myrcene(Hoseini et al 2019), menthol(Hoseini et al 2019), and berberine) helped biological receptors exposed to a variety of toxic substances to resist their biotoxicity. The results of these studies supported our observations and were consistent with the efficacy of plant supplements used in this study.Place Fig.2here3.2.2 Recommendation of CFS based on Taguchi experimental design to improve human health risks in special populationMD results showed that milk (A), egg (B), orange (C), spinach (D), grape (E), jujube (F), apple (G), and kiwi fruit (H) could significantly reduce the joint toxicity of OPFRs molecules (TCEP, TPHP, and TDCPP) in special population.…”
mentioning
confidence: 99%
“…Abdel-Tawwab et al 2018;Hamed and Abdel-Tawwab, 2017;Hoseini et al 2018aHoseini et al , 2018b.Hoseini et al found that myrcene or menthol inclusive diet inhibited ammonia-induced tissue damage, anemia, and oxidative stress responses in common carps(Hoseini et al 2019). Also, plant supplements such as garlic(Yousefi et al 2020), artemisia annulis(Taheri Mirghaed et al 2020), olea europea(Rajabiesterabadi et al 2020), ceratonia silique(Yilmaz, 2020), phytochemicals such as 1, 8 cineole(Taheri Mirghaed et al 2019), myrcene(Hoseini et al 2019), menthol(Hoseini et al 2019), and berberine) helped biological receptors exposed to a variety of toxic substances to resist their biotoxicity. The results of these studies supported our observations and were consistent with the efficacy of plant supplements used in this study.Place Fig.2here3.2.2 Recommendation of CFS based on Taguchi experimental design to improve human health risks in special populationMD results showed that milk (A), egg (B), orange (C), spinach (D), grape (E), jujube (F), apple (G), and kiwi fruit (H) could significantly reduce the joint toxicity of OPFRs molecules (TCEP, TPHP, and TDCPP) in special population.…”
mentioning
confidence: 99%